COSMIC: somatic cancer genetics at high-resolution. Issue Volume 45:Issue D1(2017) (29th November 2016) - Forbes, Simon A.; Beare, David; Boutselakis, Harry; Bamford, Sally; Bindal, Nidhi; Tate, John; Cole, Charlotte G.; Ward, Sari; Dawson, Elisabeth; Ponting, Laura; Stefancsik, Raymund; Harsha, Bhavana; et al.
Abstract: COSMIC, the Catalogue of Somatic Mutations in Cancer (http://cancer.sanger.ac.uk ) is a high-resolution resource for exploring targets and trends in the genetics of human cancer. Currently the broadest database of mutations in cancer, the information in COSMIC is curated by expert scientists, primarily by scrutinizing large numbers of scientific publications. Over 4 million coding mutations are described in v78 (September 2016), combining genome-wide sequencing results from 28 366 tumours with complete manual curation of 23 489 individual publications focused on 186 key genes and 286 key fusion pairs across all cancers. Molecular profiling of large tumour numbers has also allowed the annotation of more than 13 million non-coding mutations, 18 029 gene fusions, 187 429 genome rearrangements, 1 271 436 abnormal copy number segments, 9 175 462 abnormal expression variants and 7 879 142 differentially methylated CpG dinucleotides. COSMIC now details the genetics of drug resistance, novel somatic gene mutations which allow a tumour to evade therapeutic cancer drugs. Focusing initially on highly characterized drugs and genes, COSMIC v78 contains wide resistance mutation profiles across 20 drugs, detailing the recurrence of 301 unique resistance alleles across 1934 drug-resistant tumours. All information from the COSMIC database is available freely on the COSMIC website.